2016
DOI: 10.1016/j.jbo.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

MiR-367 negatively regulates apoptosis induced by adriamycin in osteosarcoma cells by targeting KLF4

Abstract: Diverse functions of microRNAs have been investigated in tumorigenesis in osteosarcoma (OS), involving the regulation of proliferation, invasion, migration, apoptosis and drug resistance. MiR-367 was found to be an oncogene and increased in OS. However, the function of miR-367 in drug resistance in OS cells is still unknown. In this study, we found that miR-367 was up-regulated in OS tissues and OS cell cultures. Meanwhile, treatment with adriamycin (ADR) induced apoptosis of OS cells with upregulation of miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 33 publications
1
21
0
1
Order By: Relevance
“…38 Furthermore, targeting of KLF4 contributes to apoptosis induced by Adriamycin in osteosarcoma cells. 39 In this study, our results demonstrated that KLF4 treatment inhibits growth and aggressiveness, while knockdown of KLF4 promotes growth and aggressiveness of NSCLC cells. Importantly, we found that KLF4 overexpression decreases apoptotic resistance of A549 cells induced by tunicamycin through regulation of cleaved Caspase-9, Caspase-3, Bcl-2, and Bcl-xL expression levels, which is agreed with previously reported studies.…”
Section: Discussionsupporting
confidence: 52%
“…38 Furthermore, targeting of KLF4 contributes to apoptosis induced by Adriamycin in osteosarcoma cells. 39 In this study, our results demonstrated that KLF4 treatment inhibits growth and aggressiveness, while knockdown of KLF4 promotes growth and aggressiveness of NSCLC cells. Importantly, we found that KLF4 overexpression decreases apoptotic resistance of A549 cells induced by tunicamycin through regulation of cleaved Caspase-9, Caspase-3, Bcl-2, and Bcl-xL expression levels, which is agreed with previously reported studies.…”
Section: Discussionsupporting
confidence: 52%
“…miR-367 also enhances hepatocellular carcinoma cell proliferation and invasion by regulating PTEN expression (Meng et al, 2016), and promotes pancreatic cancer invasion in vitro and metastasis in vivo through targeting of the Smad7/ TGF-β signaling pathway (Zhu et al, 2015). In addition, this miRNA suppresses Adriamycininduced apoptosis of osteosarcoma cells by targeting KLF4 (Wang et al, 2016). However, in contrast to these oncogenic characteristics, miR-367 is downregulated in gastric cancer (Bin et al, 2015), glioma (Guan et al, 2015), and cervical carcinoma (Cai et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…miR-367 has recently been identified as a novel tumor-related miRNA in colon cancer (Chae et al, 2013), breast cancer (Zhang et al, 2011), medulloblastoma (Kaid et al, 2015), esophageal squamous cell carcinoma (ESCC; Sun et al, 2016), gastric cancer (Bin et al, 2015), osteosarcoma (Wang et al, 2016), hepatocellular carcinoma (Meng et al, 2016), glioma (Guan et al, 2015), pancreatic ductal adenocarcinoma (Zhu et al, 2015), non-small cell lung cancer (NSCLC; Campayo et al, 2013), and cervical carcinoma (Cai et al, 2013). Modulation of miR-367 expression can affect several aspects of cancer cell behavior, including proliferation, apoptosis, invasion, and epithelial-to-mesenchymal transition.…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly, studies have shown that various miRNAs involved in apoptosis are also associated with chemotherapy resistance in osteosarcoma (22)(23)(24)(25). Some miRNAs function as oncogenes, and have been reported to be upregulated in osteosarcoma, while others serve as tumor suppressors, and are often downregulated in osteosarcoma (26).…”
Section: Discussionmentioning
confidence: 99%